Local Administration of Amphotericin B and Percutaneous Endoscopic Necrosectomy for Refractory Fungal-Infected Walled-Off Necrosis: A Case Report and Literature Review. Issue 6 (February 2015) - Inoue, Tadahisa; Ichikawa, Hiroshi; Okumura, Fumihiro; Mizushima, Takashi; Nishie, Hirotada; Iwasaki, Hiroyasu; Anbe, Kaiki; Ozeki, Takanori; Kachi, Kenta; Fukusada, Shigeki; Suzuki, Yuta; Sano, Hitoshi
Abstract : Abstract: Walled-off necrosis (WON) caused by fungal infection is very rare, and its treatment is more difficult than that of bacterial infection. We present the first case of a patient with refractory fungal-infected WON treated with percutaneous endoscopic necrosectomy and local administration of amphotericin B. A Japanese man in his 30s was hospitalized with severe necrotizing pancreatitis and multiple organ failure. Computed tomography imaging of the abdomen 1 month after the onset of pancreatitis revealed infected WON. Percutaneous drainage revealed purulent necrotic fluid, and culture of the fluid revealed the presence of Candida albicans and C glabrata . WON was treated by percutaneous endoscopic necrosectomy and local administration of amphotericin B. Consequently, the patient's condition improved, and Candida species were not detected in subsequent cultures. The combination of endoscopic necrosectomy with local administration of amphotericin B may be effective in treating refractory fungal-infected WON.